Analisis Fluktuasi Harga Tiga Jenis Cabai Menjelang Bulan Ramadhan di Pasar Induk Cibitung - Samsul Arifin (Jurnal Dimamu, 2026)
This study aims to analyze price fluctuations of three chili commodities—curly red chili, green bird’s eye chili, and red bird’s eye chili—during the week preceding the month of Ramadan at Cibitung Main Market. The research employed a quantitative approach using primary data collected from wholesale traders during the week preceding Ramadan for the years 2024, 2025, and 2026, corresponding to the Ramadan periods of March 2024, February–March  2025, and February 2026, respectively. Data were analyzed using descriptive price analysis, the coefficient of variation to measure price volatility, and a one-way ANOVA test to examine differences in average prices among the commodities. The results indicate that red bird’s eye chili has the highest average price at approximately IDR 77,926/kg, followed by curly red chili at around IDR 54,778/kg, while green bird’s eye chili records the lowest average price at about IDR 39,444/kg. In terms of volatility, green bird’s eye chili shows the highest coefficient of variation (approximately 0.448), indicating the greatest relative price fluctuation among the commodities. Meanwhile, curly red chili and red bird’s eye chili exhibit moderate volatility with coefficients of variation of approximately 0.250 and 0.257, respectively. The ANOVA test results show an F-value of 33.746 with a p-value < 0.05, indicating a statistically significant difference in average prices among the three chili commodities. These findings suggest that the period leading up to Ramadan is characterized by distinct price dynamics across chili types, influenced by differences in market demand and supply availability.